A New System of Cantonese Tones? Tone Perception and Production in Hong Kong South Asian Cantonese. (September 2022) - Yu, Alan C. L.; Lee, Crystal W. T.; Lan, Chen; Mok, Peggy P. K.
Studies in language contact have identified many instances of linguistic variation and grammatical innovations introduced by speakers from multi-ethnic urban neighborhoods. This study focuses on the variety of Cantonese spoken by South Asian youths in Hong Kong, specifically their production and perception of Hong Kong Cantonese tones. Our findings show that the South Asian Cantonese speakers have a smaller tonal inventory than the canonical six-tone system of standard Hong Kong Cantonese and their tonal discrimination abilities are also more impoverished relative to their ethnic Chinese peers. Further analysis shows a positive correlation between tonal discrimination accuracy and tonal realization distinctness among the South Asian speakers, but not among the ethnic Chinese. These findings suggest that South Asian Cantonese speakers might have developed a distinct tone system from their ethnic Chinese peers.